Comparison between the isokinetics parameters of shoulder joint and independence functional level in manual wheelchair users - Flores, Roberta Cardozo; Pereira, Alessandro José; Silva, Francine Casagrande Costa e; Crozara, Luciano Fernandes; Payão, Spencer Luiz Marques (Acta Fisiátrica, 2022)
Shoulder pain is a common complaint in the wheelchair user’s population. This condition brings loss of independence and quality of life. Objective: The aim of this paper is to correlate shoulder joint isokinetic parameters and independence level of manual wheelchair users with or without pain. We hypothesize that users more independent are exposed to overuse injury of shoulder joints. Method: This is an explorative cross-sectional study with a quantitative approach. Community patients attended at a Rehabilitation Center. Manual wheelchair users. Twenty-four patients participated, we used the Functional Independence Measurement (FIM) to investigate the independent level of wheeled patients and isokinetic parameters of internal/external rotators and flexion/extension muscles of shoulder joint was collected using Biodex System 4 Pro. Statistical analyses were made by Fisher Test, Spiro-Wilk Test, Pearson Correlation test, Spearman test and the Coefficient of correlation’s value was squared to estimate the percentage of variation in dependent variable, explained by independent variable. Results: Total FIM variation was between 79 and 117 and median ipsilateral strength ratio of rotator muscles were 0.94 on 75°/s and 0.95 on 150°/s for the right limb and respectively 0.96 and 0.93 for the left limb. Conclusion: Wheelchair users present internal/external rotators shoulder muscles imbalance and the covariations samples of time of injury and peak torque ratio external/internal shoulder rotators have a significant predictive value on total MIF. These results suggest that there is correlation between the studied patients and shoulder impairment.